Price and welfare effects of emission quota allocation - Rolf Golombek; Sverre A.C. Kittelsen; Knut Einar Rosendahl (Statistics Norway, Research Department, 2011)
We analyze how different ways of allocating emission quotas may influence the electricity market. Using a large-scale numerical model of the Western European energy market, we show that different allocation mechanisms can have very different effects on the electricity market, even if the total emission target is fixed. This is particularly the case if output-based allocation (OBA) of quotas is used, with gas power production substantially higher, partly at the expense of renewable and coal power, than if grandfathering and auctioning based mechanisms are used. The price of emissions is almost twice as high. Moreover, even though electricity prices are lower, the welfare costs of attaining a fixed emission target are significantly higher. The paper analyzes other allocation mechanisms as well, leading to yet more outcomes in the electricity market. The numerical results for OBA are supported by theoretical analysis, with some new general results.
Keywords: D61; H23; Q41; Q58; 330; Quota market; Electricity market; Allocation of quotas